The Determinant of Profitability of Commercial Banks in Azerbaijan - Mammadov, Parviz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
In this study, we analyzed the relationship between the profitability of banks and macroeconomic factors in Azerbaijan banking sector considering 24 banks within the period of 4 years from 2008 until 2011. In this case, we used a panel data to investi-gate that relationship. We found out that bank specific factors have more impact on the profitability of banks in Azerbaijan when compared to the macroeconomic fac-tors. With respect to the results, inflation and GDP growth rate turned out to be in-significant. We concluded by recommending some possible solutions to the problems that we came across in this study. Keywords: Bank profitability, panel data, Azerbaijan

ÖZ : Bu çalışmanın amacı, 2008-2011 yıllarını içeren dört yıllık süreçte Azerbaycan bankalarının banka kârlılığının gerek banka içsel faktörler gerekse makroekonomik faktörler baz alınarak incelenmesini içermektedir. Bu ilişkileri ampirik olarak test etmek için panel regresyon analizi uygulanmıştır. Analiz sonuçlarına göre banka karlılığına makroekonomik faktörlerin etkisinden çok içsel faktörlerin etki ettiği görülmektedir. Bunun yanında, enflasyon ve GSMH`nin oranının banka karlılığına istatistiksel olarak anlamlı bir etkisi bulunmamaktadır. Çalışmada, analiz sonucuna göre olası uygulanabilir sonuçlara da yer verilmiştir. Anahtar Kelimeler: Banka karlılığı, panel veri, Azerbaycan.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Banks and Banking - Commercial Banks - Azerbaijan; Banks and banking - Bank investments - Bank loans - Bank deposits; Bank profitability; panel data; Azerbaijan